The Effectiveness of Environmental Assessment as a Sustainable Development Tool in Developing Countries: Case of Cameroon - Ghong, Nchia Peter (Environmental Management and Sustainable Development, 2021)
In the last few decades, there has been increased worldwide awareness of the necessity to consider development from a holistic perspective, for human development without adequate environmental protection is undermined. Cameroon, like many other developing countries has made great strides in establishing and putting in place an environmental assessment system to mainstream environmental concerns into development initiatives. The full realization of this goal, however, depends on the effectiveness of the exercise which hinges principally on the provisions of relevant legislation, the institutional framework, the procedure and practice of the assessment process. Environmental assessment in many developing countries is fraught with a plethora of setbacks which can jeopardize the full contribution of the exercise to the attainment of the sustainable development goals, if not taken care of. Based on experience and field research, this study examines the current practice of environmental assessment in Cameroon, the difficulties encountered in developing countries, the chances of environmental assessment contributing to sustainability and makes recommendations on how to improve the practice in developing countries.